2012
DOI: 10.1186/gm404
|View full text |Cite
|
Sign up to set email alerts
|

A yeast phenomic model for the gene interaction network modulating CFTR-ΔF508 protein biogenesis

Abstract: BackgroundThe overall influence of gene interaction in human disease is unknown. In cystic fibrosis (CF) a single allele of the cystic fibrosis transmembrane conductance regulator (CFTR-ΔF508) accounts for most of the disease. In cell models, CFTR-ΔF508 exhibits defective protein biogenesis and degradation rather than proper trafficking to the plasma membrane where CFTR normally functions. Numerous genes function in the biogenesis of CFTR and influence the fate of CFTR-ΔF508. However it is not known whether ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(149 citation statements)
references
References 72 publications
(134 reference statements)
5
142
0
2
Order By: Relevance
“…where K functionally represents the carrying capacity (maximum culture density), l is the time to reach half-carrying capacity, and r is the maximum specific cell proliferation rate (33). Phenotypic differences were visualized by comparing growth curves between mutants in a particular column of the cell array (a single concentration) or comparison of the change in a cell proliferation parameter across the cell array.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where K functionally represents the carrying capacity (maximum culture density), l is the time to reach half-carrying capacity, and r is the maximum specific cell proliferation rate (33). Phenotypic differences were visualized by comparing growth curves between mutants in a particular column of the cell array (a single concentration) or comparison of the change in a cell proliferation parameter across the cell array.…”
Section: Methodsmentioning
confidence: 99%
“…The yeast oligomycin exporter Yor1p was chosen for this analysis because it is an MRP4 homolog whose transport activity can be scored as cell growth on oligomycin media (33,45). In addition, Yor1p possesses the conserved proline at the base of TM6 that is a feature of the ABCC subfamily (Pro-485 in Yor1p), a lysine in the outer TM collar at the same position as Lys-978 in CFTR (Lys-997 in Yor1p), and an A-loop tyrosine in NBD2 at the same location as Tyr-1219 in CFTR (Tyr-1222 in Yor1p; see alignments in Fig.…”
Section: Homologous Tm Mutations Rescue Defective Substrate Export Bymentioning
confidence: 99%
“…Identified pathways, related to the endomembrane system for synthesis and post-translational modification of membrane proteins (membranes, vesicles, ER/Golgi) and the ER stress response, have been previously implicated in CF pathophysiology, including p.Phe508del processing. 23,[33][34][35] Although the ER stress response is related to endomembrane function, the two signals (post-translational processing and ER stress response) are both pathologically relevant and are probably acting independently to modify lung disease phenotype. The strength of the genomic signatures in our results supports continued research directed at these processes for CF.…”
Section: Epigenetic Variationmentioning
confidence: 99%
“…Despite these challenges, identification of secondary modulators has proven successful across a multitude of model organisms in which the prominent role of second-site suppressors that buffer or modify traits has been established [8][9][10][11] . For example, human genetic studies have identified rare mutations in CCR5 that confer resilience against HIV infection 12 , mutations in globin genes that modify the severity of sickle cell disease by buffering primary mutations in β-globin genes 13 , and LoF mutations in PCSK9 that protect carriers from high lipid levels and resulting heart disease 14 .…”
Section: A R T I C L E Smentioning
confidence: 99%